The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/8384576
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Geniposide on Osteoarthritis by Suppressing the Activation of p38 MAPK Signaling Pathway

Abstract: It has been suggested that the activation of the p38 mitogen activated protein kinases (MAPKs) signaling pathway plays a significant role in the progression of OA by leading to the overexpression of proinflammatory cytokines, chemokines, and signaling enzymes in human osteoarthritis chondrocytes. However, most p38 MAPK inhibitors applied for OA have been thought to be limited due to their potential long-term toxicities. Geniposide (GE), an iridoid glycoside purified from the fruit of the herb, has been widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Geniposide, an iridoid glycoside in Gardenia jasminoides , exerts anti-fibrotic, anti-osteoarthritis, and anti-epilepsy actions by modulation of the expression of transforming growth factor-β (TGF-β)/Smad4, p38 mitogen-activated protein kinase (p38 MAPK), and PI3K/Akt/GSK-3beta signaling pathways, respectively [ 55 , 56 , 57 ]. Whereas, geniposide manifested a number of pathological phenomena in the liver of SD rat with the dose greater than 574 mg/kg, such as elevated MDA, liver enzymes (ALT, AST, alkaline phosphatase (ALP), total bilirubin), focal necrosis, and downregulated SOD, leading to the onset of oxidative stress caused hepatotoxicity [ 58 ].…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…Geniposide, an iridoid glycoside in Gardenia jasminoides , exerts anti-fibrotic, anti-osteoarthritis, and anti-epilepsy actions by modulation of the expression of transforming growth factor-β (TGF-β)/Smad4, p38 mitogen-activated protein kinase (p38 MAPK), and PI3K/Akt/GSK-3beta signaling pathways, respectively [ 55 , 56 , 57 ]. Whereas, geniposide manifested a number of pathological phenomena in the liver of SD rat with the dose greater than 574 mg/kg, such as elevated MDA, liver enzymes (ALT, AST, alkaline phosphatase (ALP), total bilirubin), focal necrosis, and downregulated SOD, leading to the onset of oxidative stress caused hepatotoxicity [ 58 ].…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…According to the KEGG pathway analysis, coexpressed genes in the green module mainly participate in the TNF, IL‐17, NOD‐like receptor, and MAPK signalling pathways. These pathways are mainly involved in inflammation and the progression of OA . The MAPK signalling pathway, one of intracellular serine‐threonine protein kinase superfamily members, is the centre of multiple signal transduction pathways .…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signalling pathway, one of intracellular serine‐threonine protein kinase superfamily members, is the centre of multiple signal transduction pathways . It has been suggested that the MAPK pathway activation results in the overexpression of proinflammatory cytokines, chemokines, and signalling enzymes in human OA chondrocytes, which play a significant role in the progression of OA . Blockage or inhibition of the activation of MAPK signalling can inhibit inflammatory cytokine production in OA chondrocytes to prevent the degradation of bone and cartilage .…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide (Scheme 4), an iridoid glycoside purified from fruits (most well-known Gardenia jasminoides) and herbs, has been commonly used in folk medicine for many chronic inflammatory conditions [92,93]. A 2018 study by Chen et al demonstrated that in the context of a surgically-induced OA rabbit model, this compound effectively suppressed IL-1, TNF-α, NO, and MMP-13 expression in animals synovial fluid [99]. Similar in vitro and in vivo results were obtained by Pan T. et al as the intervention promoted the production of collagen II and decreased the expression of proapoptotic molecules-Bax, Cyto-c, C-caspase 3-as opposed to an increasing Bcl-2 expression [100].…”
Section: Geniposidementioning
confidence: 99%